Non-Saccharomyces in Wine: Effect Upon Oenococcus oeni and Malolactic Fermentation - Balmaseda, Aitor; Bordons, Albert; Reguant, Cristina; Bautista-Gallego, Joaquín (Frontiers in Microbiology, 2018)
This work is a short review of the interactions between oenological yeasts and lactic acid bacteria (LAB), especially Oenococcus oeni, the main species carrying out the malolactic fermentation (MLF). The emphasis has been placed on non-Saccharomyces effects due to their recent increased interest in winemaking. Those interactions are variable, ranging from inhibitory, to neutral and stimulatory and are mediated by some known compounds, which will be discussed. One phenomena responsible of inhibitory interactions is the media exhaustion by yeasts, and particularly a decrease in L-malic acid by some non-Saccharomyces. Clearly ethanol is the main inhibitory compound of LAB produced by S. cerevisiae, but non-Saccharomyces can be used to decrease it. Sulphur dioxide and medium chain fatty acids (MCFA) produced by yeasts can exhibit inhibitory effect upon LAB or even result lethal. Interestingly mixed fermentations with non-Saccharomyces present less MCFA concentration. Among organic acids derived as result of yeast metabolism, succinic acid seems to be the most related with MLF inhibition. Several protein factors produced by S. cerevisiae inhibiting O. oeni have been described, but they have not been studied in non-Saccharomyces. According to the stimulatory effects, the use of non-Saccharomyces can increase the concentration of favorable mediators such as citric acid, pyruvic acid or other compounds derived of yeast autolysis such as peptides, glucans or mannoproteins. The emergence of non-Saccharomyces in winemaking present a new scenario in which MLF has to take place. For this reason, new tools and approaches should be explored to better understand this new winemaking context.